Psychological help for patients with cancer - Bohdan Stanovskiy (Kazimierz Wielki University, 2024)
The article represents the ethical aspects of the activity of oncology specialist, which is an important component of a comprehensive approach to the treatment and care of patients with cancer. It is noted that compliance with the ethical aspects of medical and psychological care for cancer patients requires the knowledge of oncology specialist of a wide range of physical, emotional, psychological and social effects that may arise as a result of the diagnosis and treatment of an oncopathology. The key ethical principles and their characteristics, which the oncology specialists must adhere to, are outlined. There is emphasized the importance of compliance by oncology specialists with ethical principles for the successful treatment and rehabilitation of cancer patients. Conclusions. In general, ethical aspects in psycho-oncology are an integral part of professional practice and aim to ensure maximum support, safety and respect for the rights and dignity of each patient. No code of ethics can provide an unequivocal answer to what is right in specific situations, but it serves important functions. It serves as an important basis for decision-making and provides important information to oncologists, their patients and the public about the roles and responsibilities of oncology professionals. In addition, it promotes responsible psychological practice and protection of patients from inappropriate behavior of doctors, and is used as a tool for reflection and improvement of the work of a specialist in the field of oncology.